Genome Sequence of Type Strains of Genus Stenotrophomonas - Patil, Prashant P.; Midha, Samriti; Kumar, Sanjeet; Patil, Prabhu B. (Frontiers in Microbiology, 2016)
Genomic resource of type strains and historically important strains of genus Stenotrophomonas allowed us to reveal the existence of 18 distinct species by applying modern phylogenomic criterions. Apart from Stenotrophomonas maltophilia, S. africana represents another species of clinical importance. Interestingly, Pseudomonas hibsicola, P. beteli, and S. pavani that are of plant origin are closer to S. maltophilia than the majority of the environmental isolates. The genus has an open pan-genome. By providing the case study on genes encoding metallo-β-lactamase and Clustered Regularly Interspaced Short Palindrome Repeats (CRISPR) regions, we have tried to show the importance of this genomic dataset in understanding its ecology.